1996
DOI: 10.1007/s0021663560084
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized 2-(4-hydrazinocarbonylphenyl)-4,5-diphenylimidazole as solid phase luminophore in peroxyoxalate chemiluminescence

Abstract: A new luminophore for application in peroxyoxalate chemiluminescence is presented. An analogue of the well-known chemiluminescence compound lophine, i.e. 2-(4-hydrazinocarbonylphenyl)-4,5-diphenylimidazole (HCPI), has been covalently immobilized to controlled pore glass and a porous methacrylate resin. By using this reagent in a solid phase detection reactor, sensitive determinations of hydrogen peroxide have been demonstrated. In homogeneous solution HCPI emits poorly as a result of 1,1'-oxalyldiimidazole exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[27][28][29] Applying a similar approach, Pontén et al compared six amino-based luminophores employing porous and non-porous methacrylate beads. [30][31][32] These authors concluded that porous materials were much more sensitive due to a higher surface area and degree of functionalization. To the best of our knowledge, this study from the mid-nineties is the only reported MS solid phase luminophore.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Applying a similar approach, Pontén et al compared six amino-based luminophores employing porous and non-porous methacrylate beads. [30][31][32] These authors concluded that porous materials were much more sensitive due to a higher surface area and degree of functionalization. To the best of our knowledge, this study from the mid-nineties is the only reported MS solid phase luminophore.…”
Section: Introductionmentioning
confidence: 99%
“…More than 5000 samples were injected during this period. Apart from the ease of preparation of the ISPS reactors and the fact that no frits are needed, which should be of considerable merit in many other applications, we did not experience any problems with “fines” increasing the back-pressure during long-term use. It may be concluded that this polymer composition is sufficiently rugged for practical use.…”
Section: Resultsmentioning
confidence: 96%
“…A great many procedures have been proposed to determine hydrogen peroxide. Examples include electrochemical methods (3,4), spectrophotometric methods (5,6), fluorescence techniques (7,8), and chemiluminescence methods (9,10). Nowadays, the most widely used methods for the determination of hydrogen peroxide in clinical chemistry are the spectrophotometric procedures by reaction with a chromogenic hydrogen donor substrate in the presence of peroxidase (2).…”
Section: Introductionmentioning
confidence: 99%